Adolescents with autism spectrum disorders attending special schools in Singapore : functional skills, behavioural challenges, and parental aspirations - Poon, Kenneth Kin Loong. (2011)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder identifiable from social impairments, language impairments, and a restricted range of interests and behaviours that with impairments that continue into adulthood (Howlin, Mawhood, & Rutter, 2000). In general, many of these individuals have poor employment and independent living outcomes in adulthood and there is little research on how they access the community (Howlin et al, 2000).